2011
DOI: 10.1128/aem.05715-11
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli O157:H7 on Radish Seeds by Sequential Treatments with Chlorine Dioxide, Drying, and Dry Heat without Loss of Seed Viability

Abstract: We developed and validated a treatment to inactivate Escherichia coli O157:H7 on radish seeds without decreasing seed viability. Treatments with aqueous ClO 2 followed by drying and dry-heat treatments were evaluated for efficacy to inactivate the pathogen. Conditions to dry radish seeds after treatment with water (control) or ClO 2 were established. When treated seeds with high water activity (a w ) (>0.99) were stored at 45°C and 23% relative humidity (RH), the a w decreased to <0.30 within 24 h. Drying high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 28 publications
1
20
0
2
Order By: Relevance
“…To date, no methods can completely decontaminate bacteria residing in plant seeds, and combined physical and/or chemical treatments are currently used to efficiently reduce bacterial contamination (MAFF 2003;Bang et al 2011;Ding et al 2013). Our data demonstrating the predominance of Halospirulina spp.…”
Section: Discussionmentioning
confidence: 56%
“…To date, no methods can completely decontaminate bacteria residing in plant seeds, and combined physical and/or chemical treatments are currently used to efficiently reduce bacterial contamination (MAFF 2003;Bang et al 2011;Ding et al 2013). Our data demonstrating the predominance of Halospirulina spp.…”
Section: Discussionmentioning
confidence: 56%
“…This may indicate that the resistance of MY to environmental stresses is greater than that of E. coli O157:H7 because they had colonized on the surface of spinach leaves for a longer period of time. Bang et al (2011bBang et al ( , 2011c reported that E. coli O157:H7 was more sensitive than mesophilic aerobic microorganisms or MY to environmental stresses on radish seeds. It was suggested that these microorganisms and MY were already established on the seeds prior to treatment, making them more resistant than E. coli O157:H7, which was artificially inoculated onto seeds.…”
Section: Reduction Of Microorganisms On Spinach Leaves Using Ait Sachetsmentioning
confidence: 98%
“…Treatment with either water or NaOCl followed by drying caused A C C E P T E D M A N U S C R I P T Although reports on the synergistic lethal effect of ClO 2 and drying on S. enterica have not appeared to date, reports on other foodborne pathogens exposed to these sequential treatments have been published. For example, it was found that treatment with ClO 2 followed by drying or dry heat exerted a synergistic lethal effect on E. coli O157:H7 on radish seeds (Bang et al 2011a(Bang et al , 2011b(Bang et al , 2011cKim et al, 2010). Kreske et al (2006) found that planktonic B. cereus spores exposed to ClO 2 were more sensitive to wet heat than those exposed to chlorine.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Studies in our laboratories have indicated that sequential treatment with ClO 2 and other stressors results in synergistic lethal effects against foodborne pathogens. Cells of Escherichia coli O157:H7 exposed to ClO 2 were more sensitive to desiccation (Bang et al, 2014;Kim et al, 2010) and dryheat (Bang et al, 2011a(Bang et al, , 2011b(Bang et al, , 2011c. Kreske et al (2006) reported that spores of Bacillus cereus or B. thuringiensis treated with ClO 2 had decreased tolerance to wet-heat.…”
Section: Introductionmentioning
confidence: 98%